Electrochemical performance of pre-lithiated ZnMoO4 and r-GO@ZnMoO4 composite anode for lithium-ion battery application - Bin Masood, Khalid; Parte, Golu; Jain, Neha; Dwivedi, Pravin K.; Kumar, Pushpendra; Shelke, V, Manjusha; Patel, Rp; Singh, Jai (Journal of the Taiwan Institute of Chemical Engineers, 2020)
Exploring a safer replacement of Li metal anode is crucial for technological, and fundamental importance. Li-metal is a preferred choice as anode material for lithium-ion battery (LIB) applications. However, parasitic dendritic growth on the Li metal surface during cycling causes instability and safety dreads. In the present study, we have investigated that the pre-lithiated ZnMoO4 is superior to its carbon-based counterparts (r-GO@ZnMoO4), moreover safer and sustainable than Li metal anode. The pre-lithiated ZnMoO4 delivers a better reversible capacity (similar to 1000 mAhg(-1) at 0.1 Ag-1), superior rate capability (similar to 400 mAh g(-1) at 2 Ag-1), and excellent cycling stability over 300 cycles at 0.1 Ag-1, as compared to bare ZnMoO4 and r-GO@ZnMoO4 composite. The present investigation is an attempt to provide a substitute for commonly used Li-metal/carbon anodes with better performance. (C) 2020 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Cycling stability; Electrochemistry; Li-ion battery; Nyquist plot; Rate performance; ZnMoO4 nanocomposites

Experimental and theoretical investigations of the effect of heteroatom-doped carbon microsphere supports on the stability and storage capacity of nano-Co3O4 conversion anodes for application in lithium-ion batteries - Dwivedi, Pravin K.; Nair, Aathira; Mehare, Rupali S.; Chaturvedi, Vikash; Joshi, Kavita; Shelke, V, Manjusha (Nanoscale Advances, 2020)
Conversion-type anode materials have been intensely studied for application in Li-ion batteries (LIBs) due to their potentially higher capacities than current graphite-based anodes. This work reports the development of a high-capacity and stable anode from a nanocomposite of N and S co-doped carbon spheres (NSCSs) with Co3O4 (NSCS-Co3O4). A hydrothermal reaction of saccharose withl-cysteine was carried out, followed by its carbonization. CSs when used as supports for conversion-type materials provide efficient electron/ion transfer channels, enhancing the overall electrochemical performance of the electrodes. Additionally, the heteroatoms doped in a carbon matrix alter the electronic properties, often increasing the reactivity of the carbon surface, and they are reported to be effective for anchoring metal oxide nanoparticles. Consequently, the NSCS-Co3O4 nanocomposites developed in this work exhibit enhanced and stable reversible specific capacity over several cycles. Stable cycling behavior was observed at 1 A g(-1)with 1285 mA h g(-1) of specific capacity retained after 350 cycles along with more than 99% of coulombic efficiency. This material shows excellent rate capability with a specific capacity of 745 mA h g(-1) retained even at a high current density of 5 A g(-1). Detailed DFT-based calculations revealed the role of doped supports in controlling the volume expansion upon lithiation.

Architecture of NaFe(MoO4)2 as a novel anode material for rechargeable lithium and sodium ion batteries - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Praveen, C. S.; Dwivedi, Pravin Kumari; Karbhal, Indrapal; Gosavi, Suresh W.; Shelke, V, Manjusha; Kale, Bharat B. (Applied Surface Science, 2021)
In recent decades, particular focus has been given to enhance the capacity of LIBs and SIBs either by developing new materials or by modifying existing materials. Hence, we have demonstrated a new anode material i.e. sodium iron molybdate [NaFe(MoO4)2] for both LIBs and SIBs. NaFe(MoO4)2 has been successfully synthesized by solid-state combustion technique and tested as a promising new anode material for both LIBs and SIBs. A detailed analysis of the crystal structure has been performed using DFT calculations. NaFe(MoO4)2 crystallizes in the monoclinic phase with the space group C2/c (#15). FESEM also shows highly crystalline monoclinic shaped crystals of micron size. When evaluated as an anode material for LIBs, NaFe(MoO4)2 electrode exhibited electrochemical capacity of 920 mAhg- 1 in the second cycle at the current density of 50 mAg-1. Though capacity decreases on further cycling, the coulombic efficiency was maintained at 99% for 50 cycles. Significantly, a high discharge capacity of 100 mAhg- 1 was maintained at a very high rate of 1 Ag-1. On the other hand, we have also tested NaFe(MoO4)2 for SIBs which shows excellent reversible specific capacity i.e. 100 mAhg- 1 at the current density of 100 mAg-1 even after 500 cycles. This novel system has shown good stability for LIBs and SIBs which is hitherto unattempted.
Keywords: Electrochemical study; lithium-ion battery; Morphology; NaFe(MoO4)2; Sodium-ion battery

Engineering microstructure of LiFe(MoO4)(2) as an advanced anode material for rechargeable lithium-ion battery - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Dwivedi, Pravin Kumari; Praveen, C. S.; Karbhal, Indrapal; Shelke, V, Manjusha; Kim, Bomyung; Park, Chinho; Kale, Bharat B. (Journal of Materials Science-Materials In Electronics, 2021)
Graphite is considered as an ideal anode material for lithium-ion battery (LIB) due to its high stability, good conductivity and wide source of availability. However, the low energy density and theoretical capacity of graphite cannot meet the needs of high performance anode materials. To circumvent this issue, alternative materials have been sought for many years now. Herein, we report the synthesis of highly crystalline lithium iron molybdate LiFe(MoO4)(2) by combustion method and evaluated its performance as an anode material for lithium-ion batteries. Triclinic LiFe(MoO4)(2) crystals having particle size 2-5 mu m with good crystallinity were obtained. The material shows long cycle life and high rate performance than commercial graphite and exhibits first reversible discharge capacity of 931.6 mAh/g at a current density of 100 mA/g which is three times higher than commercial graphite. The high specific capacity together with the outstanding rate and cycle performance makes LiFe(MoO4)(2) a promising anode material for LIB. A detailed analysis on the crystal structure and electronic properties of LiFe(MoO4)(2) is presented based on DFT studies to complement the experimental observations.

Resistive switching in HfO2-x/La0.67Sr0.33MnO3 heterostructures: an intriguing case of low H-field susceptibility of an E-field controlled active interface - Antad, Vivek; Shaikh, Parvez A.; Biswas, Abhijit; Rajput, Shatruhan Singh; Deo, Shrinivas; Shelke, V, Manjusha; Patil, Shivprasad; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2021)
High-performance nonvolatile resistive random access memories (ReRAMs) and their small stimuli control are of immense interest for high-speed computation and big-data processing in the emerging Internet of Things (IoT) arena. Here, we examine the resistive switching (RS) behavior in growth-controlled HfO2/La0.67Sr0.33MnO3 (LSMO) heterostructures and their tunability in a low magnetic field. It is demonstrated that oxygen-deficient HfO2 films show bipolar switching with a high on/off ratio, stable retention, as well as good endurance owing to the orthorhombic-rich phase constitution and charge (de)trapping-enabled Schottky-type conduction. Most importantly, we have demonstrated that RS can be tuned by a very low externally applied magnetic field (similar to 0-30 mT). Remarkably, application of a magnetic field of 30 mT causes RS to be fully quenched and frozen in the high resistive state (HRS) even after the removal of the magnetic field. However, the quenched state could be resurrected by applying a higher bias voltage than the one for initial switching. This is argued to be a consequence of the electronically and ionically ``active'' nature of the HfO2-x/LSMO interface on both sides and its susceptibility to the electric and low magnetic field effects. This result could pave the way for new designs of interface-engineered high-performance oxitronic ReRAM devices.
Keywords: charge trapping-detrapping; low external magnetic field; oxide-oxide interface; pulsed laser deposition; resistive switching; Schottky barrier

Honeycomb boron carbon nitride as high-performance anode material for li-ion batteries - Karbhal, Indrapal; Chaturvedi, Vikash; Patrike, Apurva; Yadav, Poonam; Shelke, V, Manjusha (ChemNanoMat, 2022)
3D Porous carbon-based materials are well known for their excellent mechanical and electrochemical properties for various energy storage applications including Li-ion Battery (LIB) anodes. However, their commercial application is limited due to their low theoretical specific capacity. Heteroatom doping in carbonaceous networks proved an efficient way to modify the surface properties, which considerably improves the Li intake capacity and Li diffusion in porous carbon materials. In this work, we have synthesized 3D honeycomb boron carbon nitride (HBCN) from boric acid, glucose, and cyanamide. Silica nanoparticles (SiO2 NPs) are used as structure-directing agents to replicate well-organized honeycomb structures. HBCN possesses a high specific surface area (SSA) of similar to 597 m(2) g(-1), with a uniform porosity distribution, low charge transfer resistance, and steady Li flux. When analyzed as an anode material for LIB, HBCN demonstrated an excellent specific capacity of similar to 652 mAhg(-1) and 408 mAhg(-1) at an input current density of 100 mAg(-1) and 1 Ag-1 respectively and an energy density of 227 Wh kg(-1) at 1 C rate in a full cell LIB. These results indicate that the doping of B and N hetero atoms is significantly advantageous for LIBs application.
Keywords: 3D-Architecture; Heteroatom Doping; High-Performance Anode; Honeycomb boron carbon nitride (HBCN); Li-ion battery

Evaluation of Fe3O4 incorporated functionalized carbon nanotube self-standing buckypaper as electrodes for solid-state symmetric supercapacitor - Bhaviripudi, Vijayabhaskara Rao; Dwivedi, Pravin K.; Pabba, Durga Prasad; Aepuru, Radhamanohar; Nakate, Umesh T.; Espinoza-Gonzalez, Rodrigo; Shelke, V, Manjusha (Journal of Energy Storage, 2023)
Iron (II, III) oxide and carbonaceous materials drawn considerable attention in energy storage owing to their special features. In this study, simple reverse co-precipitation, acid functionalization and vacuum filtration methods adopted to synthesis Fe3O4 nanoparticles of size 11 nm and -COOH acid functionalized multi-wall carbon nanotubes (FMWCNT). And further used them to prepare and optimize Fe3O4 in FMWCNT as 15 wt% and 25 wt% self-standing buckypapers of around 30-mu m thickness as electrodes for solid-state symmetric capacitor in the form of coin cell. The results show that 15 wt% and 25 wt% of Fe3O4-FMWCNT buckypapers hybrid nanostructures have Fe3O4 nanoparticles successfully incorporated in FMWCNT. The 25 wt% Fe3O4-FMWCNT electrodes with charge transfer resistance of 140 Ohm showed high areal specific capacitance (Cs) 78.5 mF/cm2 and retained 80 % of its Cs until 800 cycles even at high current density of 1 mA/cm2, scan rate of 100 mV/s whereas 15 wt% Fe3O4-FMWCNT showed low Cs of 47 mF/cm2 and retained 80 % of its Cs over 5000 cycles whereas only FMWCNT show Cs is 36 mF/cm2 with 54 Ohm. Finally, a solid-state symmetric supercapacitor coin cell with self-standing 25 wt% Fe3O4-FMWCNT buckypaper showed an excellent power density of 129.5 mW cm-3 and energy density of 3.6 mWh cm-3 is the innovation of the current work. This is mainly attributed to the combined effect of pseudocapacitive behavior from Fe3O4 by faradaic reaction with additional charge transfer resistance and electric double layer (EDLC) behavior from FMWCNTs by non-faradaic of electronic, ionic transport during charging-discharging. As-made solid-state symmetric supercapacitor appears as a high-performance storage device without extra support of current collectors for practical applications and for fabri-cation of planar capacitors.
Keywords: Buckypaper; Power density; specific capacitance; Symmetric supercapacitor

High rate, high temperature, dendrite free plating/stripping of Li in 3-dimensional honeycomb boron carbon nitride to realize an ultrastable lithium metal anode - Patrike, Apurva; Karbhal, Indrapal; Wasnik, Kundan; Torris, Arun; Maibam, Ashakiran; Krishnamurty, Sailaja; Shelke, V, Manjusha (Journal of Energy Storage, 2023)
Lithium (Li) metal could be the anode of choice for energy dense Li-batteries owing to its high theoretical specific capacity. However, low coulombic efficiency and poor safety on account of the occurrence of the Li-dendrites during charging-discharging pose a bottleneck for practical applications. In this work, we report a high-rate plating and stripping of Li through host engineering to realize ultrastable Li metal anode (LMA). Benchmark plating/stripping efficiency could be achieved via uniquely structured, highly ordered honeycomb boron carbon nitride (HBCN) as a functional scaffold. Boron and nitrogen doping, large surface area and ordered mesoporous structure induce homogeneous solid electrolyte interface (SEI) layer formation and provide numerous nucleation sites with subsequent dendrite-free growth with 99.98 % coulombic efficiency at 8 mA cm(-2) high current and 10 mAh cm(-2) capacity over 3000 cycles. Via post-cycling advanced characterizations techniques of Ex-situ XPS, 3D X-ray micro-tomography analyses and FESEM, we demonstrate the formation of a stable SEI layer and morphological changes that occurred during Li plating cycles in the HBCN structure. Computational studies validate the high lithium plating-stripping efficacy of HBCN to its highly ordered porous nature, exothermic Li-binding and upshift in the Fermi levels. When tested at elevated temperature (50 degrees C), a stable Li plating-stripping in HBCN is realised at 4 mA cm(-2) current and 10 mAh cm(-2) capacity values with similar to 100 % C.E. Furthermore, we report the results of testing a Li metal cell comprised of Li deposited HBCN anode and LiFePO4 (LFP) cathode.
Keywords: Boron carbon nitride; Dendrite-free Li metal anode; Functional scaffold; High temperature plating/stripping of Li; Molecular planarity parameter; X-ray micro-tomography

Synergistic humidity-responsive mechanical motion and proton conductivity in a cationic covalent organic framework - Das, Gobinda; Shinde, Dhanraj B.; Melapurakkal, Amrutha; Shelke, V, Manjusha; Garai, Bikash; Bazin, Philippe; Blal, Abdelhafid Ait; Benyettou, Farah; Prakasam, Thirumurugan; Halim, Rasha Abdul; Ibrahim, Fayrouzabou; Sharma, Sudhir Kumar; et al. (CHEM, 2024)
Keywords: ACTUATORS; Crystalline; DRIVEN; SOFT

Exploring FeSe2 and porous carbon composite as a cost-effective host for Al3+ in aqueous Aluminum ion batteries - Mirzapure, Vinay; Patrike, Apurva; Shelke, V, Manjusha (Electrochimica Acta, 2025)
Aluminum is a high-energy-density material with low cost, making rechargeable aluminum ion batteries (AIBs) a attractive alternative to alkali metal ion batteries. However, the practical development of aqueous AIBs is hindered by limited electrode. Herein, we report FeSe2-decorated porous nitrogen and sulfur-doped carbon spheres (FSPNSCS) as a cathode material for aqueous AIBs, with an emphasis on the reaction kinetics and electrochemical performance. FSPNSCS is synthesized through a hydrothermal approach, confirmed by comprehensive characterizations using X-ray Diffraction for crystalline structure validation and Scanning Electron Microscopy for analyzing composite morphology. Electrochemical properties and kinetics are probed using cyclic voltammetry and galvanostatic charge-discharge tests. Ex-situ XRD reveals a notable peak shift towards higher 2 theta values during discharge, indicating lattice contraction due to Al3+ insertion. Sulfur and nitrogen doping impart elasticity to the lattice structure, enhancing stability during cycling. Ex-situ XPS confirms Al3+ storage and minimal oxide formation, as further supported by microscopic elemental mapping with HRTEM. The FSPNSCS cathode achieves a reversible capacity of 60 mAh g- 1 at a current density of 200 mA g- 1. The system exhibits outstanding cycling stability, retaining over 90 % of its capacity at 500 mA g- 1 over 1000 cycles, highlighting its potential to advance aqueous AIBs for sustainable energy storage.
Keywords: Aqueous aluminum ion battery; cathode material; Electrochemistry; Transition metal selenide